Budgeting in Australia - Blöndal, Jón R.. (OECD Publishing, 2008)
This review of budgeting in Australia concentrates on the national government only. The article first discusses Australia's recent economic and fiscal performance and then focuses on the budget formulation process. After a discussion of the role of the Parliament, the article reviews various aspects of budget implementation and management. The article concludes with a special section on Australia's efforts to eliminate "red tape" within government. This review was undertaken in September 2007; following the election of a new government in Australia in November 2007, some new policies are highlighted, encompassing budget formulation, processes, accounting and management